A Zoocentric Perspective on Natural Disasters - Suzana Marjanić (Svetovi)
In this paper, written about the tragic earthquake in Banija (the 2020 Petrinja earthquake, also known as the Banovina earthquake) from a zoocentric perspective, I present several examples based on newspaper materials and conversations with activists from animal rights associations (Friends of Animals and Nature from Čakovec, Friends of Animals Croatia) on the condition and status of animal rescue operations after the Banija earthquake, which occurred during the coronavirus pandemic in Croatia. While the media published reports and photos about the coexistence of the human victims and their animals (both utilitarian animals and pets), animal rights activists came across many cases of previous (prior to the earthquake) neglect of animals.